Lithium iron phosphate material and preparation method thereof

By calcining the phosphate iron slag and dissolving the acid solution, combined with the use of acid-base regulators and stabilizers, a precursor with a sheet-like structure was prepared, and lithium iron phosphate material with excellent electrochemical properties was prepared by sintering treatment. , solves the problem of difficult recycling of phosphorus iron slag and realizes efficient recycling and recycling of lithium batteries.

CN119430120AActive Publication Date: 2025-02-14GUANGDONG GUANGHUA SCI TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411668022.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-14
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

The impurity content of phosphate iron slag is high, and it is difficult to recover, making it difficult to prepare lithium iron phosphate materials with stable electrochemical properties.

Method used

By calcining the phosphate iron slag, carbon impurities are removed; then the calcined material is dissolved in the acid solution to obtain a phosphate iron mixture; during the slurry adjustment process, the pH value of the reaction system is controlled and the The morphology of the precursor; finally, after aging, washing and drying, a precursor with a sheet-like structure was prepared, and lithium iron phosphate material was prepared by mixing and sintering with a lithium source and an organic carbon source.

Benefits of technology

It has achieved stable and excellent electrochemical performance of lithium iron phosphate materials, high discharge specific capacity, good rate performance and high first charge and discharge efficiency, solved the problem of difficult recovery of phosphate iron slag, and expanded the scope of lithium battery recycling and recycling industries. , has high economic and environmental benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430120A_ABST
    Figure CN119430120A_ABST
Patent Text Reader

Abstract

The invention relates to a lithium iron phosphate material and a preparation method thereof. The preparation method of the lithium iron phosphate material comprises the following steps: roasting ferrophosphorus slag to obtain a roasted material; dissolving the roasted material in an acid solution to obtain a ferrophosphorus mixed solution; mixing the ferrophosphorus mixed solution, an acid-base regulator, a stabilizer and a ferrophosphorus compensating agent to obtain precursor slurry; performing aging treatment, washing treatment and first drying treatment on the precursor slurry to obtain a precursor; mixing the precursor, a lithium source and an organic carbon source, and performing grinding treatment, second drying treatment and sintering treatment to obtain a lithium iron phosphate material; the stabilizer comprises a dopant and polyol grafted on the dopant; the precursor has a sheet structure, the sheet thickness is 0.02-0.2 [mu] m, the specific surface area is 7 m < 2 > / g-17 m < 2 > / g, and the tap density is 0.9 g / cm < 3 >-1.6 g / cm < 3 >. The lithium iron phosphate material has the advantages of high specific discharge capacity, high first charge-discharge efficiency, good rate capability and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of battery materials, and in particular to a lithium iron phosphate material and a preparation method thereof. Background Art

[0002] With the depletion of traditional fossil fuels and the rapid development of new energy materials, the widespread popularization of electric vehicles has become a reality. The development of power batteries with higher efficiency, higher energy density and lower cost has also become a key focus and research direction in the field of electric vehicles. At present, the pressure to reduce the cost of power batteries has increased, and lithium iron phosphate batteries have gradually surpassed ternary batteries in terms of production and installation volume due to their advantages such as high safety, long cycle life, relatively low cost and good thermal stability, and are showing a rapid growth trend. At the same time, the recycling of waste lithium iron phosphate batteries is imminent.

[0003] In traditional technology, the recycling method of waste lithium iron phosphate mainly focuses on selective lithium extraction, that is, separating high value-added lithium elements from positive electrode materials, but a large amount of ferrophosphorus slag will be produced after lithium extraction. Ferrophosphorus slag has a high impurity content and is difficult to recycle, making it difficult to prepare lithium iron phosphate materials with stable and excellent electrochemical properties. Summary of the invention

[0004] Based on this, it is necessary to provide a lithium iron phosphate material and a preparation method thereof to solve the problem that the impurity content of ferrophosphorus slag is high, the recycling is difficult, and it is difficult to prepare a lithium iron phosphate material with stable and excellent electrochemical properties.

[0005] The above-mentioned purpose of the present application is achieved through the following technical solutions:

[0006] In a first aspect of the present application, a method for preparing a lithium iron phosphate material is provided, comprising the following steps:

[0007] The ferrophosphorus slag is roasted to obtain a roasted material;

[0008] dissolving the calcined material in an acid solution to obtain a phosphorus-iron mixed solution;

[0009] Mixing the ferrophosphorus mixed solution, an acid-base regulator, a stabilizer and a ferrophosphorus compensator to obtain a precursor slurry;

[0010] Performing an aging treatment, a washing treatment and a first drying treatment on the precursor slurry to obtain a precursor;

[0011] The precursor, the lithium source and the organic carbon source are mixed, and subjected to grinding, a second drying and sintering treatment to obtain a lithium iron phosphate material;

[0012] Wherein, the stabilizer includes a dopant and a polyol;

[0013] The precursor has a flaky structure, the flaky layer thickness of the flaky structure is 0.02 μm to 0.2 μm, and the specific surface area of ​​the precursor is 7 m 2 / g~17m 2 / g, the tap density of the precursor is 0.9g / cm 3 ~1.6g / cm 3 , the D50 particle size of the precursor is 6μm~16μm.

[0014] In one embodiment, the preparation method of the stabilizer comprises the following steps:

[0015] The dopant and the polyol are mixed and ball milled to obtain the stabilizer.

[0016] In one embodiment, the dopant includes one or more of titanium dioxide, strontium oxide, ammonium metavanadate, chromium nitrate, barium nitrate, barium carbonate, aluminum oxide, aluminum nitrate, nickel oxide, magnesium oxide and magnesium carbonate.

[0017] In one embodiment, the polyol includes one or more of ethylene glycol, propylene glycol, butylene glycol, hexylene glycol, neopentyl glycol, pentaerythritol, trihydroxymethyl propane and glycerol.

[0018] In one embodiment, the mass ratio of the dopant to the polyol is (0.2~1.5):1.

[0019] In one embodiment, the mass ratio of the doping element in the dopant to the iron element in the ferrophosphorus mixture is (0.01-0.5):100.

[0020] In one embodiment, the ball milling conditions include: ball milling time of 0.1h~5h, ball milling speed of 200rpm~800rpm, material-ball ratio of (0.1~0.8):1, and ball milling medium is zirconia ceramic ball.

[0021] In one embodiment, mixing the ferrophosphorus mixed solution, the acid-base regulator, the stabilizer and the ferrophosphorus compensator comprises the following steps:

[0022] Mixing the ferrophosphorus mixed solution and the acid-base regulator to obtain a first slurry with a pH of 1.5 to 3.0;

[0023] Mixing the first slurry and the stabilizer, stirring and reacting, to obtain a second slurry;

[0024] The second slurry and the ferrophosphorus compensator are mixed so that the molar ratio of the iron element to the phosphorus element in the precursor slurry is (0.95-1.02):1.

[0025] In one embodiment, the acid-base regulator includes one or more of ammonia water, hydrogen peroxide, ammonium carbonate and ammonium bicarbonate.

[0026] In one embodiment, the stirring reaction temperature is 30°C to 70°C.

[0027] In one embodiment, the stirring reaction time is 0.5h~2h.

[0028] In one embodiment, the temperature for mixing the second slurry and the ferrophosphorus compensator is 50°C to 105°C.

[0029] In one embodiment, the phosphorus-iron compensator includes one or more of phosphoric acid, diammonium phosphate, diammonium phosphate, triammonium phosphate, iron powder, iron oxide, iron hydroxide and iron oxyhydroxide.

[0030] In one embodiment, the calcination treatment includes a fluidized bed calcination treatment, the calcination temperature is 300° C. to 550° C., and the calcination time is 2 h to 8 h.

[0031] In one embodiment, the acid in the acid solution includes one or more of hydrochloric acid, sulfuric acid, nitric acid and phosphoric acid.

[0032] In one embodiment, the concentration of the acid in the acid solution is 0.5 mol / L~5 mol / L.

[0033] In one embodiment, the temperature of the acid solution is 50°C~95°C.

[0034] In one embodiment, the molar ratio of the acid radical ions in the acid solution to the iron ions in the ferrophosphorus mixture is (1.2-3.6):1.

[0035] In one embodiment, the lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium oxalate, lithium acetate and lithium nitrate.

[0036] In one embodiment, the molar ratio of the lithium element in the lithium source to the phosphorus element in the precursor is (0.97~1.05):1.

[0037] In one embodiment, the organic carbon source includes one or more of starch, cellulose, sucrose, glucose, citric acid, chitin, Tween, polyvinyl alcohol, polyethylene glycol, polyacrylic acid and polyvinyl pyrrolidone.

[0038] In one embodiment, the mass ratio of the organic carbon source to the precursor is (3-20):100.

[0039] In one embodiment, the sintering process comprises the following steps:

[0040] In a protective atmosphere, keep warm at 650℃~830℃ for 4h~18h.

[0041] In a second aspect of the present application, a lithium iron phosphate material is provided, which is prepared by the preparation method of the lithium iron phosphate material as described above.

[0042] This application has at least the following beneficial effects:

[0043] The present application uses the ferrophosphorus slag after lithium extraction from waste lithium iron phosphate batteries as raw materials, first removes carbon impurities and other impurities that are easily oxidized and decomposed into volatile gases at high temperatures through roasting treatment, and then uses acid solution to fully leach phosphorus and iron elements to obtain a ferrophosphorus mixed solution. In the slurry adjustment process, an acid-base regulator is used to control the pH value of the reaction system, a stabilizer composed of a dopant and a polyol grafted on the dopant is used to achieve the regulation of the precursor morphology, and a ferrophosphorus compensator is used to control the phosphorus-iron ratio of the precursor, and then the precursor is obtained through aging, washing and drying. The precursor presents a flaky structure with the characteristics of regular morphology, large specific surface area, and high tap density, which is conducive to the release and embedding of lithium ions, so that the lithium iron phosphate material prepared from the precursor has the advantages of high discharge specific capacity, good rate performance, and high first charge and discharge efficiency. The preparation method of the lithium iron phosphate material provided in the present application effectively solves the problems of high impurity content and great difficulty in recycling of ferrophosphorus slag, and prepares lithium iron phosphate material with stable and excellent electrochemical properties, so that the lithium battery recovery and recycling industry is further expanded, and has high economic and environmental benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] In order to more clearly illustrate the technical solutions in the embodiments of the present application and to more completely understand the present application and its beneficial effects, the following is a brief introduction to the drawings required for the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can obtain other drawings based on these drawings without creative work.

[0045] Figure 1 is a schematic flow chart of a method for preparing a lithium iron phosphate material in an embodiment;

[0046] Figure 2 This is a SEM image of the precursor prepared in Example 3;

[0047] Figure 3 This is a SEM image of the lithium iron phosphate material prepared in Example 3;

[0048] Figure 4 This is the XRD diagram of the lithium iron phosphate material prepared in Example 3. DETAILED DESCRIPTION

[0049] In order to facilitate the understanding of the present application, the present application is further described in detail below in conjunction with specific embodiments. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.

[0050] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0051] In the present application, the meaning of "and / or" includes any and all combinations of one or more related listed items. "At least one" means more than one, such as one, two and more than two. "Multiple" or "several" means at least two, such as two, three, etc., and "multi-layer" means at least two layers, such as two layers, three layers, etc., unless otherwise clearly and specifically defined. In the description of the present application, "several" means at least one, such as one, two, etc., unless otherwise clearly and specifically defined.

[0052] When a numerical range is disclosed in this application, the above range is considered to be continuous and includes the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed in this application should be understood to include any and all subranges included therein.

[0053] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0054] In this application, "above" or "below" includes the number itself. For example, "1 below" includes 1.

[0055] The temperature parameters in this application, unless otherwise specified, are allowed to be either constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.

[0056] In the present application, room temperature refers to indoor temperature, normal temperature or general temperature. Generally speaking, the range of room temperature can be any one of the following temperature intervals: 23°C ± 2°C, 25°C ± 5°C or 20°C ± 5°C.

[0057] the term

[0058] Unless otherwise specified or there is a contradiction, the terms and phrases used in this application have the following meanings:

[0059] Particle size: For spherical particles, the particle size refers to the diameter of the spherical particles. For non-spherical particles, such as particles with an olivine morphology, the particle size usually refers to the equivalent particle size of the non-spherical particles (generally referred to as the particle size), and the particle size measured by a laser particle size analyzer is the equivalent diameter of the particle. Among them, the equivalent particle size refers to when a physical property of a particle is the same or similar to that of a homogeneous spherical particle, the diameter of the spherical particle is used to represent the diameter of the actual particle. Unless otherwise specified or there is a contradiction, the particle size in this application represents the equivalent particle size.

[0060] Particle size distribution parameters: In the particle size distribution curve of particles, the particle size corresponding to the cumulative particle size distribution percentage reaching N% is called the DN particle size, which means that the particles smaller than this particle size account for N% of all particles, where N=0~100. When N=100, the D100 particle size indicates the particle size corresponding to the cumulative particle size distribution percentage reaching 100%. When N=50, the D50 particle size is the particle size corresponding to the cumulative particle size distribution percentage reaching 50%, indicating the median particle size or median diameter, indicating that particles smaller than and larger than this particle size each account for 50%. For example, D50 particle size = 1mm, which means that particles smaller than 1mm and particles larger than 1mm each account for 50% of all particles.

[0061] Span: Also known as span, the calculation formula is: Span = (D90-D10) ÷ D50. The smaller the span, the more concentrated the particle size distribution; the larger the span, the greater the difference in particle size and the more dispersed the distribution.

[0062] In a first aspect, the present application provides a method for preparing a lithium iron phosphate material, which is used to solve the problem that the impurity content of ferrophosphorus slag is high, the recovery is difficult, and it is difficult to prepare a lithium iron phosphate material with stable and excellent electrochemical properties.

[0063] See also Figure 1, which is a schematic diagram of a process for preparing a lithium iron phosphate material in an embodiment. Figure 1 As shown, the preparation method of lithium iron phosphate material includes the following steps:

[0064] S1: roasting ferrophosphorus slag to obtain roasting material;

[0065] S2: dissolving the roasted material in acid solution to obtain a phosphorus-iron mixed solution;

[0066] S3: mixing the ferrophosphorus mixed solution, the acid-base regulator, the stabilizer and the ferrophosphorus compensator to obtain a precursor slurry;

[0067] S4: performing an aging treatment, a washing treatment and a first drying treatment on the precursor slurry to obtain a precursor;

[0068] S5: mixing the precursor, the lithium source and the organic carbon source, performing grinding treatment, a second drying treatment and a sintering treatment to obtain a lithium iron phosphate material;

[0069] The stabilizer includes a dopant and a polyol grafted onto the dopant;

[0070] The precursor has a flaky structure with a flaky layer thickness of 0.02 μm to 0.2 μm and a specific surface area of ​​7 m 2 / g~17m 2 / g, the tap density of the precursor is 0.9g / cm 3 ~1.6g / cm 3 , the D50 particle size of the precursor is 6μm~16μm.

[0071] The present application uses the ferrophosphorus slag after lithium extraction from waste lithium iron phosphate batteries as raw materials, first removes carbon impurities and other impurities that are easily oxidized and decomposed into volatile gases at high temperatures through roasting treatment, and then uses acid solution to fully leach phosphorus and iron elements to obtain a ferrophosphorus mixed solution. In the slurry adjustment process, an acid-base regulator is used to control the pH value of the reaction system, a stabilizer composed of a dopant and a polyol grafted on the dopant is used to achieve the regulation of the precursor morphology, and a ferrophosphorus compensator is used to control the phosphorus-iron ratio of the precursor, and then the precursor is obtained through aging, washing and drying. The precursor presents a flaky structure with the characteristics of regular morphology, large specific surface area, and high tap density, which is conducive to the release and embedding of lithium ions, so that the lithium iron phosphate material prepared from the precursor has the advantages of high discharge specific capacity, good rate performance, and high first charge and discharge efficiency. The preparation method of the lithium iron phosphate material provided in the present application effectively solves the problems of high impurity content and great difficulty in recycling of ferrophosphorus slag, and prepares lithium iron phosphate material with stable and excellent electrochemical properties, so that the lithium battery recovery and recycling industry is further expanded, and has high economic and environmental benefits.

[0072] The following is a detailed description of the preparation method of lithium iron phosphate material in a step-by-step manner.

[0073] S1: roasting the ferrophosphorus slag to obtain a roasted material.

[0074] It can be understood that ferrophosphorus slag is the solid waste residue after the waste lithium iron phosphate battery is pulverized and selectively extracted with lithium. Its main components are iron phosphate, carbon and a small amount of metal impurities (such as Ni, Cu or Al). It is a black-gray solid or black-gray semi-solid. In some specific examples, the ferrophosphorus slag contains the following mass fractions of elements: 28%~32% iron, 17%~19% phosphorus and 0.5%~3% carbon.

[0075] Optionally, the calcination process comprises a fluidized bed calcination process.

[0076] It can be understood that fluidized bed roasting is a process in which the material is placed in a fluidized gas for heating and roasting. It has the characteristics of high heat and mass transfer efficiency and high temperature uniformity. It can quickly and fully remove carbon and other impurities that are easily decomposed into volatile gases at high temperatures, and ensure the stable quality of the roasted material.

[0077] Optionally, the calcination temperature is 300°C to 550°C, and the calcination time is 2h to 8h. As an example, the calcination temperature includes but is not limited to 300°C, 320°C, 340°C, 360°C, 380°C, 400°C, 420°C, 440°C, 460°C, 480°C, 500°C, 520°C, 540°C or 550°C, and may further be 400°C to 500°C; the calcination time includes but is not limited to 2h, 3h, 4h, 5h, 6h, 7h or 8h, and may further be 3h to 5h.

[0078] S2: dissolving the roasted material in acid solution to obtain a phosphorus-iron mixed solution.

[0079] Optionally, the process of dissolving the roasted material in the acid solution is carried out under stirring conditions.

[0080] Optionally, the acid in the acid solution comprises sulfuric acid (H 2 SO 4 ), nitric acid (HNO 3 ) and phosphoric acid (H 3 PO 4 ) and may further be sulfuric acid (H 2 SO 4 ) or phosphoric acid (H 3 PO 4 ).

[0081] Optionally, the concentration of the acid in the acid solution is 0.5mol / L~5mol / L, including but not limited to 0.5mol / L, 1mol / L, 1.5mol / L, 2mol / L, 2.5mol / L, 3mol / L, 3.5mol / L, 4mol / L, 4.5mol / L or 5mol / L, and can further be 1mol / L~2mol / L.

[0082] Optionally, the temperature of the acid solution is 50°C to 95°C, including but not limited to 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C or 95°C, and can further be 55°C to 65°C.

[0083] Optionally, the molar ratio of the acid radical ions in the acid solution to the iron ions in the ferrophosphorus mixture is (1.2~3.6):1, including but not limited to 1.2:1, 1.4:1, 1.6:1, 1.8:1, 2.0:1, 2.2:1, 2.4:1, 2.6:1, 2.8:1, 3.0:1, 3.2:1, 3.4:1 or 3.6:1, and can further be (1.2~2.0):1.

[0084] By regulating the type, concentration, temperature and molar ratio of acid radical ions and iron ions, the roasted material can be dissolved quickly and phosphorus and iron elements can be fully leached to obtain a phosphorus-iron mixed solution.

[0085] S3: Mix the ferrophosphorus mixed solution, the acid-base regulator, the stabilizer and the ferrophosphorus compensator to obtain a precursor slurry.

[0086] Optionally, in step S3, mixing the ferrophosphorus mixed solution, the acid-base regulator, the stabilizer and the ferrophosphorus compensator comprises the following steps:

[0087] S31: mixing the phosphorus-iron mixed solution and the acid-base regulator to obtain a first slurry with a pH of 1.5 to 3.0;

[0088] S32: mixing the first slurry and the stabilizer, stirring and reacting, to obtain a second slurry;

[0089] S33: Mix the second slurry and the phosphorus iron compensator so that the molar ratio of the iron element to the phosphorus element in the precursor slurry is (0.95-1.02):1.

[0090] As an example, the pH value of the first slurry includes but is not limited to 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9 or 3.0, and can further be 1.5 to 2.0.

[0091] Optionally, the acid-base regulator includes one or more of ammonia water, hydrogen peroxide, ammonium carbonate and ammonium bicarbonate, and further can be one or more of ammonia water and hydrogen peroxide, wherein the mass fraction of ammonia water is 25% to 28%, and the mass fraction of hydrogen peroxide is 20% to 30%.

[0092] Optionally, the method for preparing the stabilizer comprises the following steps: mixing a dopant and a polyol, and performing ball milling to obtain the stabilizer.

[0093] Optionally, the dopant includes one or more of titanium dioxide, strontium oxide, ammonium metavanadate, chromium nitrate, barium nitrate, barium carbonate, aluminum oxide, aluminum nitrate, nickel oxide, magnesium oxide and magnesium carbonate, and further optionally one or more of titanium dioxide, strontium oxide and ammonium metavanadate.

[0094] It is understandable that the dopant may be selected from compounds that do not contain bound water, such as anhydrous ammonium metavanadate, or compounds that contain bound water, such as chromium nitrate nonahydrate.

[0095] Optionally, the polyol includes one or more of ethylene glycol, propylene glycol, butylene glycol, hexylene glycol, neopentyl glycol, pentaerythritol, trihydroxymethyl propane and glycerol, and further may be one or more of hexylene glycol, neopentyl glycol and pentaerythritol.

[0096] Optionally, the mass ratio of the dopant to the polyol is (0.2~1.5):1, including but not limited to 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1 or 1.5:1, and can further be (0.5~0.8):1.

[0097] Optionally, the mass ratio of the doping element in the dopant to the iron element in the ferrophosphorus mixture is (0.01~0.5):100, including but not limited to 0.01:100, 0.05:100, 0.1:100, 0.15:100, 0.2:100, 0.25:100, 0.3:100, 0.35:100, 0.4:100, 0.45:100 or 0.5:100, and can further be (0.2~0.3):100.

[0098] Optionally, the conditions for ball milling treatment include: ball milling time of 0.1h~5h, ball milling speed of 200rpm~800rpm, material-ball ratio of (0.1~0.8):1, and ball milling medium is zirconia ceramic ball.

[0099] As an example, the ball milling time includes but is not limited to 0.1h, 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h or 5h, etc., and can be further selected as 1h~2h. The ball milling speed includes but is not limited to 200rpm, 250rpm, 300rpm, 400rpm, 450rpm, 500rpm, 550rpm, 600rpm, 650rpm, 700rpm, 750rpm or 800rpm, and can be further selected as 400rpm~500rpm. The material ball ratio includes but is not limited to 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1 or 0.8:1, and can be further selected as (0.4~0.6):1.

[0100] Ball milling can produce a mechanical-chemical activation effect, which, on the one hand, reduces the particle size of the dopant, and on the other hand, increases the active sites on the surface of the dopant, promoting the grafting and coating of the polyol on the surface of the dopant, which is beneficial for the stabilizer to be evenly dispersed in the first slurry, making the material sedimentation stable while playing a decisive inducing role in the final precursor morphology, inducing the precursor to form a dense lamellar structure, and is beneficial for refining the particle size of the precursor during the drying and dehydration process.

[0101] Optionally, the stirring reaction temperature is 30°C to 70°C, including but not limited to 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C or 70°C, and can further be 50°C to 60°C.

[0102] It can be understood that before the stirring reaction, the temperature of the first slurry is controlled at 30°C to 70°C, and the temperature of the subsequent process of adding the stabilizer and the process of stirring the reaction are both controlled at 30°C to 70°C.

[0103] Optionally, the stirring reaction time is 0.5h~2h, including but not limited to 0.5h, 0.8h, 1h, 1.2h, 1.5h, 1.8h or 2h, and can further be 1h~2h.

[0104] Optionally, the temperature of mixing the second slurry and the ferrophosphorus compensator is 50°C~105°C, including but not limited to 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C or 105°C, and can be further optionally 70°C~80°C.

[0105] Optionally, the phosphorus-iron compensating agent includes one or more of phosphoric acid, diammonium phosphate, diammonium phosphate, triammonium phosphate, iron powder, iron oxide, iron hydroxide and iron oxyhydroxide.

[0106] It can be understood that the phosphorus-iron compensator includes two types: phosphorus supplement and iron supplement. The phosphorus supplement or iron supplement can be selectively added according to the molar ratio of the iron element to the phosphorus element in the second slurry, so that the molar ratio of the iron element to the phosphorus element in the precursor slurry is (0.95-1.02): 1. As an example, the molar ratio of the iron element to the phosphorus element in the precursor slurry includes but is not limited to 0.95: 1, 0.96: 1, 0.97: 1, 0.98: 1, 0.99: 1, 1: 1, 1.01: 1 or 1.02: 1, and can be further selected as (0.96-0.98): 1.

[0107] S4: performing an aging treatment, a washing treatment and a first drying treatment on the precursor slurry to obtain a precursor;

[0108] Optionally, the temperature of the aging reaction is 50°C to 105°C, including but not limited to 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C or 105°C, and can further be 70°C to 80°C.

[0109] Optionally, the aging reaction time is 2h~5h, including but not limited to 2h, 2.5h, 3h, 3.5h, 4h, 4.5h or 5h, and can further be 2h~3h.

[0110] Optionally, the washing treatment includes the following steps: washing the aged material obtained by the aging reaction with water for multiple times so that the iron content in the washing clear liquid is ≤4 mg / L and the phosphorus content is ≤200 mg / L.

[0111] Optionally, the temperature of the first drying treatment is 400°C to 800°C, including but not limited to 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C or 800°C, and can further be 550°C to 700°C.

[0112] Optionally, the time of the first drying treatment is 2 h to 8 h, including but not limited to 2 h, 3 h, 4 h, 5 h, 6 h, 7 h or 8 h, and can further be 4 h to 6 h.

[0113] Optionally, the D50 particle size of the precursor is 6 μm to 16 μm, including but not limited to 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm or 16 μm, and can further be 10 μm to 15 μm.

[0114] Optionally, the precursor has a flaky structure, and the flaky structure is stacked to form a dense structure, wherein the flaky structure has a lamella thickness of 0.02 μm to 0.2 μm, including but not limited to 0.02 μm, 0.03 μm, 0.04 μm, 0.06 μm, 0.08 μm, 0.1 μm, 0.12 μm, 0.14 μm, 0.16 μm, 0.18 μm or 0.2 μm, and may further be 0.05 μm to 0.09 μm.

[0115] Optionally, the surface area of ​​the precursor is 7 m 2 / g~17m 2 / g, including but not limited to 7m 2 / g, 8m 2 / g, 9m 2 / g, 10m 2 / g, 11m 2 / g, 12m 2 / g, 13m 2 / g, 14m 2 / g, 15m 2 / g, 16m 2 / g or 17m 2 / g, further optional to 10.7m 2 / g~13.1m 2 / g.

[0116] Optionally, the tap density of the precursor is 0.9 g / cm 3 ~1.6g / cm 3 , including but not limited to 0.9g / cm 3 , 1g / cm 3 , 1.1g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3 , 1.5g / cm 3 or 1.6 g / cm 3 , further optional to 1.28g / cm 3 ~1.41g / cm 3 .

[0117] S5: mixing the precursor, the lithium source and the organic carbon source, performing grinding treatment, a second drying treatment and a sintering treatment to obtain a lithium iron phosphate material;

[0118] Optionally, the lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium oxalate, lithium acetate and lithium nitrate, and may further be lithium carbonate.

[0119] Optionally, the molar ratio of the lithium element in the lithium source to the phosphorus element in the precursor is (0.97~1.05):1, including but not limited to 0.97:1, 0.98:1, 0.99:1, 1:1, 1.01:1, 1.02:1, 1.03:1, 1.04:1 or 1.05:1, and can be further optionally (0.99~1.02):1.

[0120] Optionally, the organic carbon source includes one or more of starch, cellulose, sucrose, glucose, citric acid, chitin, Tween, polyvinyl alcohol, polyethylene glycol, polyacrylic acid and polyvinyl pyrrolidone, and can further be one or more of sucrose, glucose, polyethylene glycol and polyacrylic acid.

[0121] It is understood that the organic carbon source can be selected from compounds that do not contain bound water, such as anhydrous glucose and anhydrous citric acid, or can be selected from compounds that contain bound water, such as monohydrated glucose and monohydrated citric acid.

[0122] Optionally, the mass ratio of the organic carbon source to the precursor is (3-20):100, including but not limited to 3:100, 4:100, 6:100, 8:100, 10:100, 12:100, 14:100, 16:100, 18:100 or 20:100, and can further be (7-10):100.

[0123] Optionally, the grinding process includes the following steps: mixing the precursor, the lithium source and the organic carbon source, and then adding water to obtain a mixture with a solid content of ≤60%; wet grinding the mixture to obtain a grinding material with a D50 particle size of 150nm~800nm.

[0124] As an example, water can be one or more of tap water, distilled water, reverse osmosis water, deionized water, pure water and ultrapure water; the solid content of the mixture includes but is not limited to 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55% or 60%, and can be further selected as 40%~50%; the D50 particle size of the abrasive includes but is not limited to 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, 550nm, 600nm, 650nm, 700nm, 750nm or 800nm, and can be further selected as 400nm~600nm.

[0125] Optionally, the second drying treatment includes the following steps: drying with a spray dryer at an inlet air temperature of 200°C to 300°C and an outlet air temperature of 90°C to 110°C to obtain a dried material with a moisture content of ≤5%.

[0126] Optionally, the sintering treatment includes the following steps: in a protective atmosphere, keeping warm at 650°C to 830°C for 4h to 18h. As an example, the protective atmosphere includes one or more of nitrogen, helium, neon, argon and xenon, and nitrogen can be further selected; the temperature of the sintering treatment includes but is not limited to 650°C, 660°C, 680°C, 700°C, 720°C, 740°C, 760°C, 780°C, 800°C, 810°C or 830°C, and can be further selected as 700°C to 800°C; the holding time of the sintering treatment includes but is not limited to 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h or 18h, and can be further selected as 6h to 10h.

[0127] Optionally, after the sintering treatment, the method further includes the following steps: subjecting the sintered material obtained by the sintering treatment to airflow pulverization treatment to obtain a lithium iron phosphate material with a D50 particle size of 0.5 μm to 2.0 μm.

[0128] As an example, the D50 particle size of the lithium iron phosphate material includes but is not limited to 0.5 μm, 0.6 μm, 0.8 μm, 1 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm or 2.0 μm, and can be further optionally 0.8 μm to 1.7 μm.

[0129] In a second aspect of the present application, a lithium iron phosphate material is provided, which is prepared by the preparation method of the lithium iron phosphate material as described above.

[0130] Optionally, the 0.1C discharge specific capacity of the lithium iron phosphate material is ≥159.2 mAh / g.

[0131] Optionally, the 0.1C first charge and discharge efficiency of the lithium iron phosphate material is ≥98%.

[0132] Optionally, the 10C discharge specific capacity of the lithium iron phosphate material is ≥123.6 mAh / g.

[0133] Optionally, the 10C / 0.1C rate of the lithium iron phosphate material is ≥77%.

[0134] The following is further described in conjunction with specific examples and comparative examples. The raw materials involved in the following specific examples and comparative examples, unless otherwise specified, can all be commercially available, the instruments used, unless otherwise specified, can all be commercially available, and the processes involved, unless otherwise specified, are conventionally selected by those skilled in the art. Among them, ferrophosphorus slag is the solid waste residue after powdering and selective lithium extraction of waste lithium iron phosphate batteries.

[0135] Example 1

[0136] The preparation method of the lithium iron phosphate material of this embodiment comprises the following steps:

[0137] (1) The ferrophosphorus slag is calcined in a fluidized bed in an air atmosphere at a calcination temperature of 450°C for a calcination time of 4 hours to obtain a calcined material.

[0138] (2) In a reaction kettle, the roasted material is dissolved in a sulfuric acid solution by continuous stirring to obtain a phosphorus-iron mixed solution; wherein the concentration of the sulfuric acid solution is 1.5 mol / L, the initial temperature is 60°C, and the molar ratio of sulfate ion to iron in the phosphorus-iron mixed solution is (1.80-1.85):1.

[0139] (3) Under stirring conditions, an acid-base regulator is added to the ferrophosphorus mixture to obtain a first slurry; the temperature of the first slurry is controlled to 52° C., a stabilizer is added, and the mixture is stirred for 1 hour to obtain a second slurry; the second slurry is preheated to 70° C., and a ferrophosphorus compensator is added dropwise to obtain a precursor slurry.

[0140] The acid-base regulator is 26 wt % ammonia water, and the pH value of the first slurry is controlled to be 1.8.

[0141] The preparation method of the stabilizer is: mixing a dopant and a polyol, and ball milling for 2 hours at a rotation speed of 450 rpm, a material-ball ratio of 0.5:1, and a ball milling medium of zirconia ceramic balls to obtain a stabilizer; wherein the dopant is titanium dioxide, and the polyol is neopentyl glycol, the mass ratio of the two is 0.6:1, and the molar ratio of the titanium element in the titanium dioxide to the iron element in the ferrophosphorus mixture is 0.26:100.

[0142] The phosphorus-iron compensator is phosphoric acid, and the molar ratio of the iron element to the phosphorus element in the precursor slurry is controlled to be 0.97:1.

[0143] (4) The precursor slurry was further aged at 70°C for 3 hours to obtain an aged material; the aged material was washed with pure water for 4 times, and the iron content in the clear liquid of the last washing was 3.62 mg / L, and the phosphorus content was 123.56 mg / L, to obtain a washed material; the washed material was transferred to a rotary kiln and dried and dehydrated at 550°C for 6 hours to obtain the desired precursor, which had a flaky structure, and the average thickness of the flaky structure was 0.06 μm, and the specific surface area was 10.7 m 2 / g, tap density is 1.36g / cm 3 , D50 particle size is 12.4μm.

[0144] (5) Mixing a precursor, a lithium source, an organic carbon source and pure water to obtain a mixture with a solid content of about 40%; performing wet grinding to obtain a ground material with a D50 particle size of 454 nm; spray drying the ground material to obtain a dry material with a moisture content of 3.4%; heating to 775°C in a pure nitrogen atmosphere and maintaining the temperature for 8.5 h, and cooling to obtain a sintered material; and air-flow crushing the sintered material to obtain a lithium iron phosphate material with a D50 particle size of 1.03 μm.

[0145] The lithium source is lithium carbonate, and the molar ratio of the lithium element of the lithium source to the phosphorus element of the precursor is 1.02:1.

[0146] The organic carbon sources are sucrose and polyacrylic acid, and the mass ratio of sucrose, polyacrylic acid and precursor is 7.2:5.3:100.

[0147] Example 2

[0148] The preparation method of the lithium iron phosphate material of this embodiment comprises the following steps:

[0149] (1) The ferrophosphorus slag is calcined in a fluidized bed in an air atmosphere at a calcination temperature of 550°C for a calcination time of 3 h to obtain a calcined material.

[0150] (2) In a reaction kettle, the roasted material is dissolved in a sulfuric acid solution by continuous stirring to obtain a ferrophosphorus mixture; wherein the concentration of the sulfuric acid solution is 1.8 mol / L, the initial temperature is 65°C, and the molar ratio of sulfate ion to iron in the ferrophosphorus mixture is (1.80-1.85):1.

[0151] (3) Under stirring conditions, an acid-base regulator is added to the ferrophosphorus mixture to obtain a first slurry; the temperature of the first slurry is controlled to 58° C., a stabilizer is added, and the mixture is stirred for 1.5 hours to obtain a second slurry; the second slurry is preheated to 75° C., and a ferrophosphorus compensator is added dropwise to obtain a precursor slurry.

[0152] The acid-base regulator is 26 wt % ammonia water, and the pH value of the first slurry is controlled to be 2.0.

[0153] The preparation method of the stabilizer is as follows: a dopant and a polyol are mixed, and the mixture is ball-milled for 2 hours at a rotation speed of 450 rpm, a material-ball ratio of 0.6:1, and a ball-milling medium of zirconia ceramic balls to obtain the stabilizer; wherein the dopant is ammonium metavanadate, and the polyol is hexanediol, and the mass ratio of the two is 0.8:1, and the molar ratio of the vanadium element in the ammonium metavanadate to the iron element in the ferrophosphorus mixture is 0.25:100.

[0154] The phosphorus-iron compensator is phosphoric acid, and the molar ratio of the iron element to the phosphorus element in the precursor slurry is controlled to be 0.98:1.

[0155] (4) The precursor slurry was further aged at 75°C for 3 hours to obtain an aged material; the aged material was washed with pure water for 4 times, and the iron content in the clear liquid of the last washing was 2.92 mg / L, and the phosphorus content was 163.96 mg / L, to obtain a washed material; the washed material was transferred to a rotary kiln and dried and dehydrated at 600°C for 4 hours to obtain the desired precursor, which had a flaky structure, and the average thickness of the flaky structure was 0.05 μm, and the specific surface area was 12.2 m 2 / g, tap density is 1.33g / cm 3 , particle size D50 is 11.3μm.

[0156] (5) Mixing a precursor, a lithium source, an organic carbon source and pure water to obtain a mixture with a solid content of about 45%; performing wet grinding to obtain a ground material with a D50 particle size of 485 nm; spray drying the ground material to obtain a dry material with a moisture content of 2.8%; heating to 768°C in a pure nitrogen atmosphere and maintaining the temperature for 9 hours, and cooling to obtain a sintered material; and air-flow crushing the sintered material to obtain a lithium iron phosphate material with a D50 particle size of 1.22 μm.

[0157] The lithium source is lithium carbonate, and the molar ratio of the lithium element of the lithium source to the phosphorus element of the precursor is 1.015:1.

[0158] The organic carbon sources are anhydrous glucose and Tween, and the mass ratio of anhydrous glucose, Tween and precursor is 9.2:1.6:100.

[0159] Example 3

[0160] The preparation method of the lithium iron phosphate material of this embodiment comprises the following steps:

[0161] (1) The ferrophosphorus slag is calcined in a fluidized bed in an air atmosphere at a temperature of 500°C for a time of 3 h to obtain a calcined material.

[0162] (2) In a reaction kettle, the roasted material is dissolved in a sulfuric acid solution by continuous stirring to obtain a ferrophosphorus mixture; wherein the concentration of the sulfuric acid solution is 1.8 mol / L, the initial temperature is 65°C, and the molar ratio of sulfate ion to iron in the ferrophosphorus mixture is (1.9-2.0):1.

[0163] (3) Under stirring conditions, an acid-base regulator is added to the ferrophosphorus mixture to obtain a first slurry; the temperature of the first slurry is controlled to 54° C., a stabilizer is added, and the mixture is stirred for 2 h to obtain a second slurry; the second slurry is preheated to 72° C., and a ferrophosphorus compensator is added dropwise to obtain a precursor slurry.

[0164] The acid-base regulator is selected from 26wt% ammonia water and 25wt% hydrogen peroxide, the volume ratio of the two is 1:1, and the pH value of the first slurry is controlled to be 2.0.

[0165] The preparation method of the stabilizer is as follows: a dopant and a polyol are mixed, and the mixture is ball-milled for 2 hours at a rotation speed of 500 rpm, a material-ball ratio of 0.4:1, and a ball-milling medium of zirconia ceramic balls to obtain a first stabilizer and a second stabilizer. In the first stabilizer, the dopant is ammonium metavanadate, the polyol is hexanediol, the mass ratio of the two is 0.8:1, and the molar ratio of the vanadium element in the ammonium metavanadate to the iron element in the ferrophosphorus mixed solution is 0.22:100; in the second stabilizer, the dopant is titanium dioxide, the polyol is neopentyl glycol, the mass ratio of the two is 0.6:1, and the molar ratio of the titanium element in the titanium dioxide to the iron element in the ferrophosphorus mixed solution is 0.15:100.

[0166] The phosphorus-iron compensator is phosphoric acid, and the molar ratio of the iron element to the phosphorus element in the precursor slurry is controlled to be 0.98:1.

[0167] (4) The precursor slurry was further aged at 72°C for 3 hours to obtain an aged material; the aged material was washed with pure water for 5 times, and the iron content in the clear liquid of the last washing was 2.22 mg / L, and the phosphorus content was 93.54 mg / L, to obtain a washed material; the washed material was transferred to a rotary kiln and dried and dehydrated at 700°C for 4 hours to obtain the desired precursor, which had a flaky structure, and the average lamella thickness of the flaky structure was 0.07 μm, and the specific surface area was 13.1 m 2 / g, tap density is 1.41g / cm 3 , particle size D50 is 10.4μm.

[0168] (5) Mixing a precursor, a lithium source, an organic carbon source and pure water to obtain a mixture with a solid content of about 45%; performing wet grinding to obtain a ground material with a D50 particle size of 515 nm; spray drying the ground material to obtain a dry material with a moisture content of 3.3%; heating to 770°C in a pure nitrogen atmosphere and maintaining the temperature for 8 hours, and cooling to obtain a sintered material; and air-flow crushing the sintered material to obtain a lithium iron phosphate material with a D50 particle size of 1.09 μm.

[0169] The lithium source is lithium carbonate, and the molar ratio of the lithium element of the lithium source to the phosphorus element of the precursor is 1.006:1.

[0170] The organic carbon sources are anhydrous glucose and polyvinyl alcohol, and the mass ratio of anhydrous glucose, polyvinyl alcohol and precursor is 8.5:5.3:100.

[0171] Example 4

[0172] The preparation method of the lithium iron phosphate material of this embodiment comprises the following steps:

[0173] (1) The ferrophosphorus slag is calcined in a fluidized bed in an air atmosphere at a temperature of 500°C for a time of 3 h to obtain a calcined material.

[0174] (2) In a reaction kettle, the roasted material is dissolved in a phosphoric acid solution by continuous stirring to obtain a phosphorus-iron mixed solution; wherein the concentration of the phosphoric acid solution is 2 mol / L, the initial temperature is 55°C, and the molar ratio of the phosphate ion to the iron element in the phosphorus-iron mixed solution is (1.2-1.4):1.

[0175] (3) Under stirring conditions, an acid-base regulator is added to the ferrophosphorus mixture to obtain a first slurry; the temperature of the first slurry is controlled to 58° C., a stabilizer is added, and the mixture is stirred for 2 h to obtain a second slurry; the second slurry is preheated to 70° C., and a ferrophosphorus compensator is added to obtain a precursor slurry.

[0176] The acid-base regulator is selected from 26wt% ammonia water and 25wt% hydrogen peroxide, the volume ratio of the two is 1:1, and the pH value of the first slurry is controlled to be 1.6.

[0177] The preparation method of the stabilizer is as follows: a dopant and a polyol are mixed, and the mixture is ball-milled for 1 hour at a rotation speed of 500 rpm, a material-ball ratio of 0.4:1, and a ball-milling medium of zirconium oxide ceramic balls to obtain the stabilizer; wherein the dopant is strontium oxide, the polyol is pentaerythritol, the mass ratio of the two is 0.5:1, and the molar ratio of the vanadium element in the strontium oxide to the iron element in the ferrophosphorus mixture is 0.23:100.

[0178] The ferrophosphorus compensator is iron powder, and the molar ratio of the iron element to the phosphorus element in the precursor slurry is controlled to be 0.985:1.

[0179] (4) The precursor slurry was further aged at 70°C for 2.5 hours to obtain an aged material; the aged material was washed with pure water for 4 times, and the iron content in the clear liquid of the last washing was 3.47 mg / L, and the phosphorus content was 183.92 mg / L to obtain a washed material; the washed material was transferred to a rotary kiln and dried and dehydrated at 700°C for 4 hours to obtain the desired precursor, which had a flaky structure, and the average thickness of the flaky structure was 0.06 μm, and the specific surface area was 12.6 m 2 / g, tap density is 1.29g / cm 3 , particle size D50 is 11.9μm.

[0180] (5) Mixing a precursor, a lithium source, an organic carbon source and pure water to obtain a mixture with a solid content of about 40%; performing wet grinding to obtain a ground material with a D50 particle size of 418 nm; spray drying the ground material to obtain a dry material with a moisture content of 3.5%; heating to 770°C in a pure nitrogen atmosphere and maintaining the temperature for 8 hours, and cooling to obtain a sintered material; and air-flow crushing the sintered material to obtain a lithium iron phosphate material with a D50 particle size of 0.95 μm.

[0181] The lithium source is lithium carbonate, and the molar ratio of the lithium element of the lithium source to the phosphorus element of the precursor is 0.996:1.

[0182] The organic carbon sources are sucrose and polyacrylic acid, and the mass ratio of sucrose, polyacrylic acid and precursor is 7.3:6.6:100.

[0183] Example 5

[0184] This embodiment is basically the same as embodiment 4, except that the fluidized bed calcination in step (1) is replaced by ordinary calcination. The preparation method of the lithium iron phosphate material in this embodiment includes the following steps:

[0185] 1) The ferrophosphorus slag is calcined in an air atmosphere at a temperature of 500°C for 3 hours to obtain a calcined material.

[0186] (2) In a reaction kettle, the roasted material is dissolved in a phosphoric acid solution by continuous stirring to obtain a phosphorus-iron mixed solution; wherein the concentration of the phosphoric acid solution is 2 mol / L, the initial temperature is 55°C, and the molar ratio of the phosphate ion to the iron element in the phosphorus-iron mixed solution is (1.2-1.4):1.

[0187] (3) Under stirring conditions, an acid-base regulator is added to the ferrophosphorus mixture to obtain a first slurry; the temperature of the first slurry is controlled to 58° C., a stabilizer is added, and the mixture is stirred for 2 h to obtain a second slurry; the second slurry is preheated to 70° C., and a ferrophosphorus compensator is added to obtain a precursor slurry.

[0188] The acid-base regulator is selected from 26wt% ammonia water and 25wt% hydrogen peroxide, the volume ratio of the two is 1:1, and the pH value of the first slurry is controlled to be 1.6.

[0189] The preparation method of the stabilizer is as follows: a dopant and a polyol are mixed, and the mixture is ball-milled for 1 hour at a rotation speed of 500 rpm, a material-ball ratio of 0.4:1, and a ball-milling medium of zirconium oxide ceramic balls to obtain the stabilizer; wherein the dopant is strontium oxide, the polyol is pentaerythritol, the mass ratio of the two is 0.5:1, and the molar ratio of the vanadium element in the strontium oxide to the iron element in the ferrophosphorus mixture is 0.23:100.

[0190] The ferrophosphorus compensator is iron powder, and the molar ratio of the iron element to the phosphorus element in the precursor slurry is controlled to be 0.985:1.

[0191] (4) The precursor slurry was further aged at 70°C for 2.5 hours to obtain an aged material; the aged material was washed with pure water for 4 times, and the iron content in the clear liquid of the last washing was 3.68 mg / L, and the phosphorus content was 193.32 mg / L to obtain a washed material; the washed material was transferred to a rotary kiln and dried and dehydrated at 700°C for 4 hours to obtain the desired precursor, which had a flaky structure, and the average thickness of the flaky structure was 0.09 μm, and the specific surface area was 11.6 m 2 / g, tap density is 1.28g / cm 3 , particle size D50 is 14.7μm.

[0192] (5) Mixing a precursor, a lithium source, an organic carbon source and pure water to obtain a mixture with a solid content of about 40%; performing wet grinding to obtain a ground material with a D50 particle size of 424 nm; spray drying the ground material to obtain a dry material with a moisture content of 3.7%; heating to 770°C in a pure nitrogen atmosphere and maintaining the temperature for 8 hours, and cooling to obtain a sintered material; and air-flow crushing the sintered material to obtain a lithium iron phosphate material with a D50 particle size of 0.99 μm.

[0193] The lithium source is lithium carbonate, and the molar ratio of the lithium element of the lithium source to the phosphorus element of the precursor is 0.996:1.

[0194] The organic carbon sources are sucrose and polyacrylic acid, and the mass ratio of sucrose, polyacrylic acid and precursor is 7.3:6.6:100.

[0195] Comparative Example 1

[0196] The preparation method of the lithium iron phosphate material of this embodiment comprises the following steps:

[0197] (1) The ferrophosphorus slag is calcined in an air atmosphere at a temperature of 500°C for 3 hours to obtain a calcined material.

[0198] (2) In a reaction kettle, the roasted material is dissolved in a phosphoric acid solution by continuous stirring to obtain a phosphorus-iron mixed solution; wherein the concentration of the phosphoric acid solution is 2 mol / L, the initial temperature is 55°C, and the molar ratio of the phosphate ion to the iron element in the phosphorus-iron mixed solution is (1.2-1.4):1.

[0199] (3) Under stirring conditions, an acid-base regulator is added to the ferrophosphorus mixture to obtain a first slurry; the temperature of the first slurry is controlled to 58° C., no stabilizer is added, and the reaction is stirred for 2 hours to obtain a second slurry; the first slurry is preheated to 70° C., and a ferrophosphorus compensator is added dropwise to obtain a precursor slurry.

[0200] The acid-base regulator is selected from 26wt% ammonia water and 25wt% hydrogen peroxide, the volume ratio of the two is 1:1, and the pH value of the first slurry is controlled to be 1.6.

[0201] The ferrophosphorus compensator is iron powder, and the molar ratio of the iron element to the phosphorus element in the precursor slurry is controlled to be 0.985:1.

[0202] (4) The precursor slurry was further aged at 70°C for 2.5 hours to obtain an aged material; the aged material was washed with pure water for 4 times, and the iron content in the clear liquid of the last washing was 5.46 mg / L, and the phosphorus content was 282.34 mg / L, to obtain a washed material; the washed material was transferred to a rotary kiln and dried and dehydrated at 700°C for 4 hours to obtain the desired precursor, which had a loose flaky structure, many fragmented points, and a specific surface area of ​​9.6 m 2 / g, tap density is 1.12g / cm 3 , particle size D50 is 18.8μm.

[0203] (5) Mixing a precursor, a lithium source, an organic carbon source and pure water to obtain a mixture with a solid content of about 40%; performing wet grinding to obtain a ground material with a D50 particle size of 423 nm; spray drying the ground material to obtain a dry material with a moisture content of 3.7%; heating to 770°C in a pure nitrogen atmosphere and maintaining the temperature for 8 hours, and cooling to obtain a sintered material; and air-flow crushing the sintered material to obtain a lithium iron phosphate material with a D50 particle size of 1.13 μm.

[0204] The lithium source is lithium carbonate, and the molar ratio of the lithium element of the lithium source to the phosphorus element of the precursor is 0.996:1.

[0205] The organic carbon sources are sucrose and polyacrylic acid, and the mass ratio of sucrose, polyacrylic acid and precursor is 7.3:6.6:100.

[0206] Comparative Example 2

[0207] This comparative example is basically the same as Example 4, except that: in step (3), the stabilizer does not contain pentaerythritol, but only contains dopant strontium oxide, and the strontium oxide is ball-milled for 1 hour under the same conditions.

[0208] Comparative Example 3

[0209] This comparative example is basically the same as Example 4, except that: the stabilizer in step (3) does not contain strontium oxide as a dopant, but only contains pentaerythritol, and the pentaerythritol is ball-milled for 1 hour under the same conditions.

[0210] Comparative Example 4

[0211] This comparative example is basically the same as Example 4, except that the stabilizer in step (3) is replaced by a mixture of strontium oxide and pentaerythritol, and no ball milling treatment is performed.

[0212] Test Case

[0213] 1. Test method

[0214] 1. Scanning electron microscope (SEM) test: The sample is fixed with conductive glue or adhesive tape, the instrument uses an accelerating voltage of 5kv, and the test is observed in a vacuum state. The results are shown in Figure 2~Figure 3 , and observed the structural parameters of the sample (sheet thickness, D10 particle size, D50 particle size and D90 particle size), and calculated the diameter distance according to (D90-D10) / D50. The results are shown in Tables 1 and 2. Among them, Figure 2 This is the SEM image of the precursor obtained in Example 3. Figure 3 This is the SEM image of the lithium iron phosphate material prepared in Example 3.

[0215] 2. X-ray powder diffraction (XRD) test: test scanning speed 5° / min, angle range 5°~90°, results are shown in Figure 4 .

[0216] 3. Specific surface area (BET) test: The adsorption gas is nitrogen and the degassing condition is 200℃ for 2h.

[0217] 4. Tap density: Weigh 50 g of sample, put it into a 100 mL measuring cylinder, place the measuring cylinder on a vibration device, and vibrate it 3000 times.

[0218] 5. Electrochemical performance test: Weigh lithium iron phosphate material, conductive agent SP and binder PVDF in a mass ratio of 90:5:5, add NMP and ball grind for 4 hours, apply it on the surface of aluminum foil and dry it at 120℃, then roll, make sheets and assemble. The negative electrode is a lithium sheet, and the electrolyte is 1mol / L LiPF 6 The solution, whose solvent is ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1, is assembled into a button cell with a polypropylene microporous membrane as a separator. The battery test system is used to test the charge and discharge performance at room temperature. The test voltage range is 2.0~3.80V. The same battery assembly and test are performed on commercially available products of the same type. The battery's 0.1C first discharge specific capacity, 0.1C first charge and discharge efficiency, 10C first discharge specific capacity, and 10C / 0.1C rate are recorded. The results are shown in Table 2.

[0219] Depend on Figure 2 It can be seen that the precursor prepared in Example 3 has a flaky structure, and the flaky structures are stacked to form a dense structure, which is conducive to the preparation of lithium iron phosphate materials with stable performance.

[0220] Depend on Figure 3 It can be seen that the lithium iron phosphate material prepared in Example 3 has a spherical structure with relatively uniform particle size and high sphericity, and the carbon coating effect is good, which plays an important role in stabilizing the performance of the material.

[0221] Depend on Figure 4 It can be seen that the XRD curve of the lithium iron phosphate material prepared in Example 3 is consistent with the lithium iron phosphate standard card, with no impurity peaks and no impurity phases, indicating that the material is a lithium iron phosphate material with good crystallinity.

[0222] As shown in Table 1, the precursors prepared in Examples 1 to 5 all have a flaky and dense structure, with a flaky layer thickness of 0.05 μm to 0.09 μm, a D50 particle size of 10.4 μm to 14.7 μm, and a specific surface area of ​​10.7 m 2 / g~13.1m 2 / g, tap density is 1.28g / cm 3 ~1.41g / cm 3 Compared with Examples 1 to 5, the precursors prepared in Comparative Examples 1 to 4 exhibited a loose flaky structure with more fragmentary points and a significantly lower tap density.

[0223] As can be seen from Table 2, the lithium iron phosphate materials obtained in Examples 1 to 5 are all spherical structures, with a D50 particle size of 0.95 μm to 1.22 μm and a diameter distance of 2.03 to 2.48. Compared with Examples 1 to 5, the lithium iron phosphate materials obtained in Comparative Examples 1 to 4 are quasi-spherical structures with lower sphericity, a significantly larger diameter distance, and reduced particle size uniformity.

[0224] It can be seen from Table 3 that after the lithium iron phosphate materials prepared in Examples 1 to 5 are used as positive electrode materials to be assembled into button cells, the 0.1C discharge specific capacity of the battery can reach more than 159.2 mAh / g, the 0.1C first charge and discharge efficiency is stable at more than 98%, the 10C discharge specific capacity can reach more than 123.6 mAh / g, and the 10C / 0.1C rate is stable at more than 77%, which is significantly higher than that of Comparative Examples 1 to 4 and commercially available products.

[0225] Table 1. Precursor related parameters

[0226]

[0227] Table 2. Related parameters of lithium iron phosphate

[0228]

[0229] Table 3. Electrochemical performance of button cells

[0230]

[0231] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0232] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of protection of the present application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the scope of protection of the present application. Therefore, the scope of protection of the present application shall be subject to the attached claims.

Claims

1. A method for preparing a lithium iron phosphate material, characterized in that: The following steps are involved: The ferrophosphorus slag is roasted to obtain a roasted material; dissolving the calcined material in an acid solution to obtain a phosphorus-iron mixed solution; Mixing the ferrophosphorus mixed solution, an acid-base regulator, a stabilizer and a ferrophosphorus compensator to obtain a precursor slurry; Performing an aging treatment, a washing treatment and a first drying treatment on the precursor slurry to obtain a precursor; The precursor, the lithium source and the organic carbon source are mixed, and subjected to grinding, a second drying and sintering treatment to obtain a lithium iron phosphate material; Wherein, the stabilizer includes a dopant and a polyol grafted onto the dopant; The precursor has a flaky structure, the flaky layer thickness of the flaky structure is 0.02 μm to 0.2 μm, and the specific surface area of ​​the precursor is 7 m 2 / g~17m 2 / g, the tap density of the precursor is 0.9g / cm 3 ~1.6g / cm 3 , the D50 particle size of the precursor is 6μm~16μm.

2. The method for preparing the lithium iron phosphate material according to claim 1, characterized in that: The preparation method of the stabilizer comprises the following steps: The dopant and the polyol are mixed and ball milled to obtain the stabilizer.

3. The method for preparing the lithium iron phosphate material according to claim 2, characterized in that: One or more of the following conditions are met: (1) The dopant includes one or more of titanium dioxide, strontium oxide, ammonium metavanadate, chromium nitrate, barium nitrate, barium carbonate, aluminum oxide, aluminum nitrate, nickel oxide, magnesium oxide and magnesium carbonate; (2) The polyol includes one or more of ethylene glycol, propylene glycol, butylene glycol, hexylene glycol, neopentyl glycol, pentaerythritol, trihydroxymethylpropane and glycerol; (3) The mass ratio of the dopant to the polyol is (0.2-1.5):1; (4) The mass ratio of the doping element in the dopant to the iron element in the ferrophosphorus mixed solution is (0.01-0.5):100; (5) The ball milling conditions include: ball milling time of 0.1h~5h, ball milling speed of 200rpm~800rpm, material-ball ratio of (0.1~0.8):1, and ball milling medium of zirconia ceramic ball.

4. The method for preparing the lithium iron phosphate material according to any one of claims 1 to 3, characterized in that: Mixing the ferrophosphorus mixed solution, the acid-base regulator, the stabilizer and the ferrophosphorus compensator comprises the following steps: Mixing the ferrophosphorus mixed solution and the acid-base regulator to obtain a first slurry with a pH of 1.5 to 3.0; Mixing the first slurry and the stabilizer, stirring and reacting, to obtain a second slurry; The second slurry and the ferrophosphorus compensator are mixed so that the molar ratio of the iron element to the phosphorus element in the precursor slurry is (0.95-1.02):

1.

5. The method for preparing the lithium iron phosphate material according to claim 4, characterized in that: One or more of the following conditions are met: (1) The acid-base regulator includes one or more of ammonia water, hydrogen peroxide, ammonium carbonate and ammonium bicarbonate; (2) The stirring reaction temperature is 30°C to 70°C; (3) The stirring reaction time is 0.5h~2h; (4) The temperature of mixing the second slurry and the ferrophosphorus compensating agent is 50° C. to 105° C.; (5) The phosphorus-iron compensating agent includes one or more of phosphoric acid, diammonium phosphate, diammonium phosphate, triammonium phosphate, iron powder, iron oxide, iron hydroxide and iron oxyhydroxide.

6. The method for preparing the lithium iron phosphate material according to claim 4, characterized in that: The calcination process includes a fluidized bed calcination process, the calcination temperature is 300° C. to 550° C., and the calcination time is 2 h to 8 h.

7. The method for preparing the lithium iron phosphate material according to claim 4, characterized in that: One or more of the following conditions are met: (1) The acid in the acid solution includes one or more of sulfuric acid, nitric acid and phosphoric acid; (2) The acid concentration in the acid solution is 0.5 mol / L to 5 mol / L; (3) The temperature of the acid solution is 50°C to 95°C; (4) The molar ratio of the acid radical ions in the acid solution to the iron ions in the ferrophosphorus mixture is (1.2-3.6):

1.

8. The method for preparing the lithium iron phosphate material according to any one of claims 1 to 3 and 5 to 7, characterized in that: One or more of the following conditions are met: (1) The lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium oxalate, lithium acetate and lithium nitrate; (2) The molar ratio of the lithium element in the lithium source to the phosphorus element in the precursor is (0.97-1.05):1; (3) The organic carbon source includes one or more of starch, cellulose, sucrose, glucose, citric acid, chitin, Tween, polyvinyl alcohol, polyethylene glycol, polyacrylic acid and polyvinyl pyrrolidone; (4) The mass ratio of the organic carbon source to the precursor is (3-20):

100.

9. The method for preparing the lithium iron phosphate material according to claim 8, characterized in that: The sintering process comprises the following steps: In a protective atmosphere, keep warm at 650℃~830℃ for 4h~18h.

10. A lithium iron phosphate material, characterized in that: The lithium iron phosphate material is prepared by the preparation method of the lithium iron phosphate material according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for recycling battery-grade lithium carbonate and iron phosphate from waste lithium iron phosphate powder

    CN117383590A

  • Doped ferrous lithium phosphate, preparation method therefor and use thereof

    WO2024045566A1